2006
DOI: 10.1080/01421590600627516
|View full text |Cite
|
Sign up to set email alerts
|

What to do about medical students with unsatisfactory consultation skills?

Abstract: If it is accepted that new doctors must be 'Fit to Practice' in a standard clinical house job, they should be competent in basic communication skills. Although these skills may be assessed as part of a routine OSCE-style exam in the course of the curriculum, the question is raised whether students who fail to demonstrate a minimal level of competence in this area should to be allowed to progress to the next stage of the course and eventually graduate. This paper describes our experiences with introducing 'barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…These findings are at odds with those of a number of studies that have evaluated performance on written or clinical examinations before and after a specific remediation intervention 7,14–38 and concluded that the intervention was effective. However, single studies ‘are limited in the generalisability of the knowledge they produce about concepts, populations, settings and times’ and ‘frequently illuminate only one part of a larger explanatory puzzle’ 39 .…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…These findings are at odds with those of a number of studies that have evaluated performance on written or clinical examinations before and after a specific remediation intervention 7,14–38 and concluded that the intervention was effective. However, single studies ‘are limited in the generalisability of the knowledge they produce about concepts, populations, settings and times’ and ‘frequently illuminate only one part of a larger explanatory puzzle’ 39 .…”
Section: Introductionmentioning
confidence: 66%
“…Remediation in medical education appears to be an increasingly important area of research: the majority ( n = 23, 74%) of studies were published after 2000 7,14–17,19–22,24,27–31,33,34,37,38,51–54 . and 11 of these were published from 2009 onwards 14–16,20,29,31,34,38,52–54 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dowell and colleagues used 'barrier' stations in communication skills in their OSCE. Students who failed these stations, irrespective of their overall exam performance, had to undertake a compulsory 2-week module in CCS followed by assessment before being allowed to progress [25]. …”
Section: Discussionmentioning
confidence: 99%
“…To improve the clinical competencies of poor performing students, tailored education programs are required [10,11,12,13]. However, the medical education literature is relatively lacking in effective methodological strategies or verifications [14,15,16].…”
Section: Introductionmentioning
confidence: 99%